2021
DOI: 10.1155/2021/4202019
|View full text |Cite
|
Sign up to set email alerts
|

Direct DNA Sequencing-Based Analysis of Microbiota Associated with Hematological Malignancies in the Eastern Province of Saudi Arabia

Abstract: Introduction. Bloodstream infections (BSI) among patients with hematological malignancies (HM) could predispose them to higher morbidity and mortality for various underlying conditions. Several microorganisms, either pathogenic or opportunistic normal human flora, could cause severe bacteremia and septicemia. While conventional methods have their own limitations, molecular methods such as next-generation sequencing (NGS) can detect these blood infections with more reliability, specificity, and sensitivity, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…10 to no. 19), mNGS was able to identify additional pathogens from the blood samples compared with conventional methods. Aside from bacteria, the extra information provided by mNGS was mainly virus, including CMV, human mastadenovirus C, and herpes simplex virus type 1, which was discovered from seven pa- Our study showed that mNGS and conventional diagnostic methods reached comparable positive results in nine cases (case no.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…10 to no. 19), mNGS was able to identify additional pathogens from the blood samples compared with conventional methods. Aside from bacteria, the extra information provided by mNGS was mainly virus, including CMV, human mastadenovirus C, and herpes simplex virus type 1, which was discovered from seven pa- Our study showed that mNGS and conventional diagnostic methods reached comparable positive results in nine cases (case no.…”
Section: Resultsmentioning
confidence: 98%
“…10 to no. 19), eight (53.3%) patients had blood sampled prior to effective antimicrobial agents given and four (26.7%) patients had blood sampled on the same day when fever flared-up. For three patients, more information was required by conventional diagnostic methods (case no.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdulhaq et al studied the tongue microbiota of children with autism spectrum disorder (ASD) in Jazan city and noted that there was no significant difference in the microbiota compared to that of healthy children [ 83 ]. Analysis of bacterial metagenome from blood samples of Saudi Arabian blood cancer patients with bloodstream infections showed the predominance of Gram-negative bacteria (82%) in which E. coli and K. pneumonia were higher [ 84 ]. Based on amplicon and metagenome sequencing, various bacteria associated with pneumonia, namely Acinetobacter baumannii , Pseudomonas aeruginosa and Streptococcus pneumonia , and several ARGs were reported to be present in the oropharyngeal swabs, tracheal aspirates, and throat swabs samples of Saudi patients infected with Middle East respiratory syndrome CoV (MERS-CoV) [ 85 ].…”
Section: Saudi Arabian Microbiome Studies On Human Healthmentioning
confidence: 99%
“…However, conventional microbiological tests (CMTs) have competitive weaknesses, such as long turnaround time, complex process, low positive rate, and throughput. Metagenomic next-generation sequencing (mNGS), by contrast, directly detects the nucleic acid sequence of microorganisms in clinical specimens, skipping microbial culture (Gu et al 2019;Alzahrani et al 2021;Zhang et al 2020), and covers a variety of pathogenic microorganisms including viruses, bacteria, fungi, and parasites quickly and objectively (Gu et al 2019;Petersen et al 2020). Here, we exemplified an old man who had clinically suspected viral encephalitis and was ultimately diagnosed as fungal cerebral vasculitis using mNGS.…”
Section: Introductionmentioning
confidence: 99%